Unraveling binding mechanism and kinetics of macrocyclic Gαq protein inhibitors. (November 2021) - Voss, Jan H.; Nagel, Jessica; Rafehi, Muhammad; Guixà-González, Ramon; Malfacini, Davide; Patt, Julian; Kehraus, Stefan; Inoue, Asuka; König, Gabriele M.; Kostenis, Evi; Deupi, Xavier; Namasivayam, Vigneshwaran; et al.
Abstract: G proteins represent intracellular switches that transduce signals relayed from G protein-coupled receptors. The structurally related macrocyclic depsipeptides FR900359 (FR) and YM-254890 (YM) are potent, selective inhibitors of the Gαq protein family. We recently discovered that radiolabeled FR and YM display strongly divergent residence times, which translates into significantly longer antiasthmatic effects of FR. The present study is aimed at investigating the molecular basis for this observed disparity. Based on docking studies, we mutated amino acid residues of the Gαq protein predicted to interact with FR or YM, and recombinantly expressed the mutated Gαq proteins in cells in which the native Gαq proteins had been knocked out by CRISPR-Cas9. Both radioligands showed similar association kinetics, and their binding followed a conformational selection mechanism, which was rationalized by molecular dynamics simulation studies. Several mutations of amino acid residues near the putative binding site of the "lipophilic anchors" of FR, especially those predicted to interact with the isopropyl group present in FR but not in YM, led to dramatically accelerated dissociation kinetics. Our data indicate that the long residence time of FR depends on lipophilic interactions within its binding site. The observed structure-kinetic relationships point to a complex binding mechanism of FR, which likely involves snap-lock- or dowel-like conformational changes of either ligand or protein, or both. These experimental data will be useful for the design of compounds with a desired residence time, a parameter that has now been recognized to be of utmost importance in drug development. Graphical Abstract: ga1